Increased blood level of urea and creatinine after chemotherapy in breast cancer patients - Raza, Uzma; Iftikhar, Ali; Khanam, Aziza; Rizwan, Sidra (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is treated with surgery and often combined with chemotherapy, radiotherapy and or hormonal therapy or both. The treatment has some side effects such as hair loss, nausea, fatigue peripheral neuropathy, nephropathy etc. The objective of the study was to assess the nephrotoxic effects after treatment of breast cancer. Methods: The infiltrating ductal carcinoma patients were treated with surgery, chemotherapy, with or without radiotherapy and hormonal therapy. The non-diabetic, non-cardiac post-menopausal breast cancer patients were further subdivided on the basis of nodes histopathology, with or without lymph node metastasis. Patients were subjected to different combination of disciplines of therapy including radiotherapy, chemotherapy and hormonal therapy. The blood samples were collected before and after chemotherapy. The blood was analyzed for urea and creatinine to assess the nephrotoxicity. Results: There was a significant increase in blood urea and creatinine levels after the treatment as compared to before the start of therapy. Conclusions: It is concluded that treatment of cancer (with chemotherapy, radiotherapy, hormonal therapy) lead to nephrotoxicity.